Discretization and numerical realization of contact problems for elastic‐perfectly plastic bodies. PART II – numerical realization, limit analysis. Issue 12 (21st January 2015) - Cermak, M.; Haslinger, J.; Kozubek, T.; Sysala, S.
Abstract : Two numerical methods based on the variational formulation in terms of stresses are analyzed: the semi‐smooth Newton method with damping and the alternating direction method of multipliers. These methods are used for tracking the loadings path to determine the discretized limit loading parameter and for solving elastic‐perfectly plastic problems. Abstract : The paper deals with numerical realization of discretized, frictionless static contact problems for elastic‐perfectly plastic materials and the computational limit analysis. Two numerical methods based on the variational formulation in terms of stresses are analyzed: the semi‐smooth Newton method with damping and the alternating direction method of multipliers. These methods are used for tracking the loadings path to determine the discretized limit loading parameter and for solving elastic‐perfectly plastic problems.